Exposure to silicone oil endotamponades induces VEGF antibody aggregation and loss of functionality - Wohlfart, Sabrina; Herth, Jonathan; Böhmann, Manuel Ben; Pander, Giulia; Herbster, Lorenz; Mier, Walter; Auffarth, Gerd U.; Uhl, Philipp; Hammer, Maximilian (Investigative ophthalmology & visual science, 2024)
To investigate the interaction of a common monoclonal antibody (bevacizumab) with silicone oils and vitreous substitute hydrogels. Protein content (spectrophotometry) and bioactivity (ELISA) of bevacizumab were assessed after direct contact to silicone oil and vitreous substitute hydrogels up to 24 hours. To detect antibody aggregation, particle size was determined by dynamic light scattering. Changes in secondary protein structure were assessed using circular dichroism. Experiments were translated to another antibody, trastuzumab, because its bioactivity can be additionally quantified by its binding to the membrane of HER2-positive cells. The functionality of bevacizumab gradually decreased during exposure to silicone oils with only 30% of activity remaining after 24 hours. Although circular dichroism did not reveal structural changes, the particle size increased drastically, indicating antibody aggregation for both antibodies. Exposure to silicone oil strongly reduced binding of trastuzumab to HER2-positive cells. The addition of polysorbate, a common stabilizer for antibody formulations, dose-dependently prevented aggregation, with 62% aggregation observed at 0.04% polysorbate compared to only 10% aggregation at 0.5% polysorbate. No aggregation occurred after exposure to vitreous body replacement hydrogels. Contact to silicone oils induces a major loss of functionality of bevacizumab and trastuzumab. This limits clinical use during silicone oil tamponade. The beneficial effect of adding polysorbate suggests that loss of solubilizer is a likely cause of aggregation. Hydrogels, alternatives for vitreous body replacement, do not impair antibody functionality.
Gesehen am 12.03.2025